Arranjos produtivos locais e custos de transação : um estudo comparativo dos arranjos capixabas de vestuário (Colatina) e rochas ornamentais (Cachoeiro de Itapemirim) - Silva Júnior, Sérgio Manhans da (2007)
It presents the main concepts on clusters, with emphasis in the term of local productive arrangements , arguing in critical way the absence of elements that make possible one better agreement of the relations Inter-firms. It is used in the attempt to improve this concept, the theory of transaction costs, with emphasis on the question of the specific assets, making correlation it enters the degree of developments of local productive arrangements and the presence of these assets. In this intention, it is used as case study, for verification of this hypothesis, two productive arrangements from the state of Espirito Santo, that are analyzed in a comparative form, in order to verify the impact of different levels of specific assets on the degree of maturity of the arrangement. Finally, it is noticed a direct relation among those elements, wich makes that the presence of greaters levels of assets has important impact on the competitive advantage of the arrangements